Low levels of realized seed and pollen gene flow and strong spatial genetic structure in a small, isolated and fragmented population of the tropical tree Copaifera langsdorffii Desf - Sebbenn, A. M.; Carvalho, A. C. M. [UNESP]; Freitas, M. L. M.; Moraes, S. M. B. [UNESP]; Gaino, Ana Paula da Silva de Campos [UNESP]; da Silva, J. M. [UNESP]; Jolivet, C.; Moraes, M. L. T. [UNESP] (Nature Publishing Group, 2011)
Over the past century, the Brazilian Atlantic forest has been reduced to small, isolated fragments of forest. Reproductive isolation theories predict a loss of genetic diversity and increases in inbreeding and spatial genetic structure (SGS) in such populations. We analysed eight microsatellite loci to investigate the pollen and seed dispersal patterns, genetic diversity, inbreeding and SGS of the tropical tree Copaifera langsdorffii in a small (4.8 ha), isolated population. All 112 adult trees and 128 seedlings found in the stand were sampled, mapped and genotyped. Seedlings had significantly lower levels of genetic diversity (A 16.5+/-0.45, mean+/-95% s.e.; H(e) 0.838+/-0.006) than did adult trees (A = 23.2+/-0.81; H(e) = 0.893+/-0.030). Parentage analysis did not indicate any seed immigration (m(seeds) = 0) and the pollen immigration rate was very low (m(pollen) = 0.047). The average distance of realized pollen dispersal within the stand was 94m, with 81% of the pollen travelling <150m. A significant negative correlation was found between the frequency and distance of pollen dispersal (r=-0.79, P<0.01), indicating that short-distance pollinations were more frequent. A significant SGS for both adults (similar to 50 m) and seedlings (similar to 20 m) was also found, indicating that most of the seeds were dispersed over short distances. The results suggested that the spatial isolation of populations by habitat fragmentation can restrict seed and pollen gene flow, increase SGS and affect the genetic diversity of future generations. Heredity (2011) 106, 134-145; doi:10.1038/hdy.2010.33; published online 7 April 2010
Keywords: Copaifera langsdorffii; tropical trees; microsatellite loci; seed dispersal; pollen dispersal; spatial genetic structure